PERANCANGAN ILUSTRASI KAOS OTOCUL - Akbar Alfianto Prayitno; Hendro Aryanto (Desgrafia, 2025)
Otocul is a Brand that stands for Automotive, a term used to discuss all things related to transportation, Regarding vehicle components and various systems in it itself are studied in the Engineering category and also Culture which means the diversity of social forms produced by people either from the same or different genetic types or can be called culture. The target market is aimed at teenagers aged 17-25 years who are especially fond of automotive. One alternative to provide an understanding to the public about the automotive world, especially custom motorbikes with design designs that of course describe the brand identity that will attract the target market. With the existence of the Otocul brand, indirectly the public can get to know more about custom motorbikes and the automotive world.